Integrating GIS into traffic incident management: A web-based system - Anuar, Aina Najeehah; Kurk, Wei Yi; Kamal Baharin, Safiza Suhana; Mohd Noor, Nisfariza (RSIS International, 2025)
The increasing frequency and severity of road accidents in Malaysia, driven by a significant disparity between vehicle growth and infrastructure capacity, present a pressing need for advanced traffic management solutions. This study details the design, development, and evaluation of a Web-GIS Traffic Incident Management System (WGTIMS), an integrated platform designed to enhance incident reporting, spatial visualization, and multi-stakeholder coordination. The system was constructed using a structured methodology of planning, design, development, and implementation, with deliberate integrations for performance and security. Built on an open-source stack (PHP, MySQL, Leaflet.js), WGTIMS employs a role-based architecture to serve administrators, police officers, and public users. A rigorous evaluation strategy was employed, combining black-box testing with preliminary user feedback. The technical testing demonstrated that the system successfully met all specified functional requirements, with test cases for critical workflows—including user authentication, incident reporting, and spatial data visualization, yielding the expected outcomes and robust error handling. User sessions indicated that the interface was intuitive and the GIS visualization was particularly effective for situational awareness. These findings confirm that WGTIMS is a viable and robust platform for improving response times and analytical decision-making in traffic incident management. Future work will focus on large-scale field deployment, cloud integration, and incorporating AI models for predictive analytics to further elevate its operational impact.